The Use Of A Behavioristic Approach In Improving Live Skills In Children With Special Needs In Bireuen State SLB - Marsitah, Iis; Annisa, Cut Nyak; Rainapia, Rainapia; Yani, Sahrafitri; Oktari, Erlina (Sean Institute, 2023)
Behavioristic learning theory is a learning theory that prioritizes changes in student behavior as a result of stimulus and response. In other words, learning is a form of change experienced by students in terms of their abilities aimed at changing behavior by means of interaction between stimulus and response. Thus, behavioristic learning theory focuses more on developing student behavior in a better direction. Life skills are students' skills to understand themselves and their potential in life, which includes goal setting, problem solving and living with others, among other things. For children with special needs, learning General Life Skills aims to function as education according to their goals, namely developing the human potential of students to be able to face their roles in the future. This research raises the issue of life skills learning or live skills for children with special needs in SLB schools. The purpose of this study is to find out how to implement programs or live skills learning for children with special needs in special schools. The research took place at SLB Negeri Bireuen. The research method used is the case study method and the data obtained by conducting interviews with teachers at the school. The application of live skills at SLB Negeri Bireuen is in the form of training and visits to places such as factories and markets. Children who are involved in life skill activities that are carried out once a month are all children with special needs in the school taking into account the characteristics and conditions of the child. The purpose of this study is to find out how to implement programs or live skills learning for children with special needs in special schools. The research took place at SLB Negeri Bireuen. The research method used is the case study method and the data obtained by conducting interviews with teachers at the school. The application of live skills at SLB Negeri Bireuen is in the form of training and visits to places such as factories and markets. Children who are involved in life skill activities that are carried out once a month are all children with special needs in the school taking into account the characteristics and conditions of the child. The purpose of this study is to find out how to implement programs or live skills learning for children with special needs in special schools. The research took place at SLB Negeri Bireuen. The research method used is the case study method and the data obtained by conducting interviews with teachers at the school. The application of live skills at SLB Negeri Bireuen is in the form of training and visits to places such as factories and markets. Children who are involved in life skill activities that are carried out once a month are all children with special needs in the school taking into account the characteristics and conditions of the child. The research method used is the case study method and the data obtained by conducting interviews with teachers at the school. The application of live skills at SLB Negeri Bireuen is in the form of training and visits to places such as factories and markets. Children who are involved in life skill activities that are carried out once a month are all children with special needs in the school taking into account the characteristics and conditions of the child. The research method used is the case study method and the data obtained by conducting interviews with teachers at the school. The application of live skills at SLB Negeri Bireuen is in the form of training and visits to places such as factories and markets. Children who are involved in life skill activities that are carried out once a month are all children with special needs in the school taking into account the characteristics and conditions of the child.